100 attend World Sustainable Construction Conference Series 2024 - Nor Azlin, Mohd Azman (UMPSA, 2024)
KUALA LUMPUR, 18 October 2024 - The World Sustainable Construction Conference Series 2024 (WSCC 2024), organised by the Faculty of Civil Engineering Technology (FTKA), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), was held physically and online from 18 to 19 October 2024 at the Seri Pacific Hotel, Kuala Lumpur.